Evaluation of the Effectiveness of the Clinical Learning Assessment System in Nursing Educational Institutions - Hardjito S. Darmojo; M. Adila Rossa; Al-Bahra (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2020)
Clinical learning assessment is an essential component of nursing education because it plays a direct role in ensuring comprehensive and continuous student competency achievement. An effective clinical assessment system not only serves to assess final learning outcomes but also supports the learning process through constructive and objective feedback. This study aims to evaluate the effectiveness of the clinical learning assessment system in nursing educational institutions in terms of validity, reliability, learning feedback, and student satisfaction. The study used a quantitative design with a cross-sectional survey approach. The study sample consisted of 220 nursing students who had participated in clinical practice, selected using a stratified random sampling technique. Data were collected through a structured questionnaire that had been tested for content validity and internal reliability. Data analysis was conducted using descriptive and inferential statistics, including reliability tests, difference tests, and multiple linear regression analysis. The results showed that the effectiveness of the clinical learning assessment system was categorized as good. All assessment dimensions had high reliability values, indicating the consistency of the instrument used. Student satisfaction was the dimension with the highest score and had a significant influence on clinical competency achievement. Furthermore, there were differences in perceptions of the effectiveness of the assessment system based on the students' educational level. The conclusion of this study confirms that a standardized, objective, and meaningful feedback-supported clinical learning assessment system can improve the quality of clinical learning and support nursing students' competency achievement. The results of this study are expected to serve as a basis for developing and refining clinical assessment systems in nursing educational institutions.